Asian wild rice is a hybrid swarm with extensive gene flow and feralization from domesticated rice - Wang, Hongru; Vieira, Filipe G.; Crawford, Jacob E.; Chu, Chengcai; Nielsen, Rasmus (Genome Research, 2017)
The domestication history of rice remains controversial, with multiple studies reaching different conclusions regarding its origin(s). These studies have generally assumed that populations of living wild rice, O. rufipogon, are descendants of the ancestral population that gave rise to domesticated rice, but relatively little attention has been paid to the origins and history of wild rice itself. Here, we investigate the genetic ancestry of wild rice by analyzing a diverse panel of rice genomes consisting of 203 domesticated and 435 wild rice accessions. We show that most modern wild rice is heavily admixed with domesticated rice through both pollen- and seed-mediated gene flow. In fact, much presumed wild rice may simply represent different stages of feralized domesticated rice. In line with this hypothesis, many presumed wild rice varieties show remnants of the effects of selective sweeps in previously identified domestication genes, as well as evidence of recent selection in flowering genes possibly associated with the feralization process. Furthermore, there is a distinct geographical pattern of gene flow from aus, indica, and japonica varieties into colocated wild rice. We also show that admixture from aus and indica is more recent than gene flow from japonica, possibly consistent with an earlier spread of japonica varieties. We argue that wild rice populations should be considered a hybrid swarm, connected to domesticated rice by continuous and extensive gene flow.
10.1101/gr.204800.116